CULTURAL ASPECTS OF BREASTFEEDING IN ASIAN COUNTRIES: A SYSTEMATIC REVIEW - Dewi Hestiani K; Nur, Rezeki; S, Tri Damatanty (Media Inovasi Pendidikan dan Publikasi, 2023)
Breastfeeding is essential for maternal and infant health, playing a crucial role in achieving several Sustainable Development Goals (SDGs). However, cultural factors such as traditions, social norms, and economic conditions greatly influence breastfeeding practices across Asia, leading to significant regional variations. This systematic review aims to assess how cultural factors shape breastfeeding decisions in Asia and to explore how these factors interact with social norms and health policies. The PRISMA method was applied to search three databases (PubMed, Scopus, and Google Scholar) using keywords related to breastfeeding and Asian culture. 300 articles were identified, with 9 selected for in-depth analysis after applying inclusion and exclusion criteria. Cultural beliefs, such as the rejection of colostrum and the influence of family authority, significantly delay breastfeeding initiation in countries like Indonesia and Vietnam. Social norms in India encourage early breastfeeding initiation, but patriarchal systems in South Asia limit exclusive breastfeeding. The COVID-19 pandemic added complexity, influencing mothers' decisions. Cultural factors play a significant role in shaping breastfeeding practices across Asia. Culturally sensitive interventions are needed to address these challenges, promote exclusive breastfeeding, and improve maternal and infant health outcomes. Further research is recommended to explore effective interventions tailored to cultural contexts and investigate the impact of urbanization and modernization on breastfeeding practices.